2018
DOI: 10.1039/c8ra03620a
|View full text |Cite
|
Sign up to set email alerts
|

Current progress, challenges and future prospects of diagnostic and therapeutic interventions in Alzheimer's disease

Abstract: The diverse pathological mechanisms and their implications for the development of effective diagnostic and therapeutic interventions in Alzheimer's disease are presented with current progress, challenges and future prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 153 publications
(169 reference statements)
1
118
0
Order By: Relevance
“…In pathological conditions, APP is cleaved by β‐ and γ‐secretases to generate perilous peptides Aβ1 to 37/43. Aβ42 is highly hydrophobic and undergoes aggregation to form polymorphic species, such as oligomers, protofibrils, fibrillar aggregates and senile plaques, that cause neurodegeneration and memory deficiencies (Figure ) …”
Section: Protein Cleavage (Generation Accumulation and Aggregation Omentioning
confidence: 99%
See 3 more Smart Citations
“…In pathological conditions, APP is cleaved by β‐ and γ‐secretases to generate perilous peptides Aβ1 to 37/43. Aβ42 is highly hydrophobic and undergoes aggregation to form polymorphic species, such as oligomers, protofibrils, fibrillar aggregates and senile plaques, that cause neurodegeneration and memory deficiencies (Figure ) …”
Section: Protein Cleavage (Generation Accumulation and Aggregation Omentioning
confidence: 99%
“…A recent report revealed that 47 million people were affected by AD worldwide in 2015; this is expected to reach more than 135 million by 2050 . The number of deaths caused by major diseases, such as cancer, cardiovascular, and AIDS, are declining due to the availability of effective medication, whereas those as a result of AD have risen by more than 71 % . Thus, AD is a devastating disease that causes distress in patients and is a major health‐related economic burden to society .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimer's disease (AD) is a progressive and fatal neurodegenerative disease in which the deposition of extracellular senile plaques and the intracellular neurofibrillary tangles are the main hallmarks. [1][2][3] The deposition or misfolding of amyloid-β peptide (Aβ) is associated with the formation of senile plaques and therefore considered to be a key diagnostic target. [4,5] Aβ is derived from the amyloid precursor protein by sequential cleavage, via βand γ-secretases.…”
Section: Introductionmentioning
confidence: 99%